Marie-Grace makes a difference - Buckey, Sarah Masters, 1955- (American girls collection., 2011)
As the yellow fever epidemic continues to ravage New Orleans and the orphanages become more crowded, Marie-Grace and Cécile help with the orphans, until Marie-Grace learns that her Uncle Luc's fiancée, Mademoiselle Océane, has fallen ill.